Polyol Pathway Exacerbated Ischemia/Reperfusion-Induced Injury in Steatotic Liver. (20th May 2014) - Zhang, Changhe; Huang, Changjun; Tian, Yuan; Li, Xiangcheng
Abstract : Background . The polyol pathway, a bypass pathway of glucose metabolism initiated by aldose reductase (AR), has been shown to play an important role in mediating tissue ischemia/reperfusion (I/R) impairment recently. Here, we investigated how and why this pathway might affect the fatty liver following I/R. Methods . Two opposite models were created: mice with high-fat-diet-induced liver steatosis were treated with aldose reductase inhibition (ARI) and subsequent I/R; and AR-overexpressing L02 hepatocytes were sequentially subjected to steatosis and hypoxia/reoxygenation. We next investigated (a) the hepatic injuries, including liver function, histology, and hepatocytes apoptosis/necrosis; (b) the NAD(P)(H) contents, redox status, and mitochondrial function; and (c) the flux through the caspase-dependent apoptosis pathway. Results . AR-inhibition in vivo markedly attenuated the I/R-induced liver injuries, maintained the homeostasis of NAD(P)(H) contents and redox status, and suppressed the caspase-dependent apoptosis pathway. Correspondingly, AR overexpression in vitro presented the opposite effects. Conclusion . The flux through the polyol pathway may render steatotic liver greater vulnerability to I/R. Interventions targeting this pathway might provide a novel adjunctive approach to protect fatty liver from ischemia.